2016
DOI: 10.1007/s00520-016-3079-4
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte growth factor use in elderly patients with non-Hodgkin’s lymphoma in the United States: adherence to guidelines and comparative effectiveness

Abstract: Purpose The efficacy of prophylactic granulocyte colonystimulating factors (G-CSFs) among elderly patients with non-Hodgkin's lymphoma (NHL) receiving CHOP-based chemotherapy has been demonstrated in clinical trials, and G-CSFs are recommended in guidelines. We studied guideline adherence and the effectiveness of G-CSFs in the general population. Methods We used inpatient and outpatient claims from nationally representative databases linked to cancer information from tumor registries. Patients (N = 5884) diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It is difficult to relate results from this study with published literature because prior studies have focused on specific regimens, 17 regimens with high risk for FN, 18 any chemotherapy, 24 or elderly Medicare enrollees. 15 In their study using four health insurance databases from 2002 to 2005 (Medicare, Medicaid, and 2 commercial), Ramsey 15 The increase in use of CSF observed in this study aligns with findings from previous publications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to relate results from this study with published literature because prior studies have focused on specific regimens, 17 regimens with high risk for FN, 18 any chemotherapy, 24 or elderly Medicare enrollees. 15 In their study using four health insurance databases from 2002 to 2005 (Medicare, Medicaid, and 2 commercial), Ramsey 15 The increase in use of CSF observed in this study aligns with findings from previous publications.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 There is no recent data regarding changes in chemotherapy regimens by FN risk category, changes in primary prophylactic-CSF use, and incidence of NRH in commercially insured cancer patients. Available studies are limited to single cancer types with older data 17 or selected regimens. 18…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of 5884 patients over age 65 using SEER data found that clinicians’ adherence to guidelines recommending primary G-CSF prophylaxis in elderly patients with NHL receiving anthracycline-based chemotherapy now approaches 70 % in the USA [61•]. Primary prophylaxis reduced the risk of outpatient encounters for fever or infection but did not have an impact on inpatient encounters or deaths during cycle 1 of chemotherapy.…”
Section: Supportive Care For Treatment-related Issuesmentioning
confidence: 99%
“…Short-acting recombinant granulocyte colony stimulating factors (G-CSFs; filgrastim (Neupogen ® ), tbo-filgrastim (Granix ® )) are used as both prophylaxis and treatment of severe or febrile neutropenia caused by myelosuppressive chemotherapy [1][2][3][4]. In 2015, the US Food and Drug Administration (FDA) approved the first filgrastim biosimilar, filgrastim-sndz (Zarxio ® ), for prophylaxis and treatment of chemotherapy-induced neutropenia, with a second biosimilar, filgrastim-aafi (Nivestym ® ) being approved in 2018 [5].…”
Section: Introductionmentioning
confidence: 99%